NWD1 facilitates synaptic transmission and contributes to neuropathic pain. (1st March 2022) - Wu, Yanqiong; Fu, Qiaochu; Huang, Xiaoxia; Luo, Yifan; Wan, Shengjun; Peng, Minjing; Su, Shanchun; Xu, Xueqin; Li, Yang; Li, Xiaohui; Sun, Dongsheng; Ke, Changbin
Abstract: Neuropathic pain is the most common symptom for which patients seek medical attention. Existing treatments to control pain are largely ineffective because of poor understanding the underlying mechanisms. Synaptic plasticity is fundamental to the spinal sensitivity of neuropathic pain. In the present study, we showed that SNL induced significant allodynia and hyperalgesia as well as upregulation of Nwd1 and GluN2B, which were reversed by knockdown of NWD1. Electrophysiological experiments demonstrated that SNL enhanced synaptic transmission, which was prevented by knockdown of NWD1. In vitro experiments showed that knockdown of NWD1 inhibited dendritic growth and synaptogenesis. Taken together, our results suggest that NWD1 enhances synaptic transmission and contributes to the development of neuropathic pain by enhancing GluN2B synaptic expression and anchor and promoting excitatory synaptogenesis. Highlights: Upregelation of NWD1 contributes to neuropathic pain. NWD1 enhances synaptic transmission. NWD1 induces GluN2B synaptic expression and synaptogenesis.